Bolehkah wanita menjadi imam negara - Koderi, M (Jakarta : Gema Insani Press, 1999)
Women as state leader in Indonesia; Islamic viewpoint
Includes bibliographical references (p. 115-118) and index
Keywords: Women heads of state -- Indonesia; Muslim women -- Indonesia; Women in Islam -- Indonesia